Performance analysis of a wireless MAN - Rufino, José (2008)
A wireless network with metropolitan coverage was created to fulfill the data communication requirements for the Bragança Digital City program, part of the portuguese Digital Cities initiative. The wireless Metropolitan Area Network, based on IEEE 802.11b, still provides both a performant and an economical solution, tailored to the application scenario. Performance measurements have been done in order to apprehend the real network throughput under typical user applications and to have insight into other network characteristics. A comparison with a wired counterpart is also provided.